2014
DOI: 10.5489/cuaj.1407
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of urethral strictures treated by endoscopic urethrotomy and urethroplasty

Abstract: Introduction: We analyze the outcomes of patients with urethral stricture who underwent surgical treatment within the past 5 years. Methods: This is a retrospective study of male patients who underwent surgery for urethral stricture at our service from January 2008 to June 2012. We analyzed the comorbidities, type, length and location of the stricture and the surgical treatment outcome after endoscopic urethrotomy, urethroplasty or both. Results: In total, 45 patients with a mean age of 53.7 ± 16.7 years under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…On the contrary, urethroplasty was traditionally considered a difficult surgical procedure and reserved for much more complex cases, although advanced with better longterm cure rates (Singh et al, 2011). However, it has been demonstrated that endoscopic surgery was superior to urethroplasty as long as the stricture did not exceed 2 cm in length, given its low morbidity and rapid convalescence (Wright et al, 2006;Hameed et al, 2011;Veeratterapillay and Pickard, 2012;Tinaut-Ranera et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, urethroplasty was traditionally considered a difficult surgical procedure and reserved for much more complex cases, although advanced with better longterm cure rates (Singh et al, 2011). However, it has been demonstrated that endoscopic surgery was superior to urethroplasty as long as the stricture did not exceed 2 cm in length, given its low morbidity and rapid convalescence (Wright et al, 2006;Hameed et al, 2011;Veeratterapillay and Pickard, 2012;Tinaut-Ranera et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have proven that MIT procedure has quite similar results as compared to EPA procedure on many aspects such as QoL, IPSS score, urine residue, recurrence, erectile function as assessed by EHS score, Qmax value, and overall satisfaction measured by PPS [13]. By having those results, we showed that MIT procedure is not inferior as compared to EPA in the management of partial posterior urethral strictures in our institution.…”
Section: Discussionmentioning
confidence: 51%
“…By having those results, we showed that MIT procedure is not inferior as compared to EPA in the management of partial posterior urethral strictures in our institution. However, until recently, EPA is still deemed as a gold standard of treatment in the management of posterior urethral strictures in many studies [13], [14]. The results in this study do not attempt to against what has been decided as a gold standard in posterior urethral stricture management.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, stricture recurrence is commonplace when managing strictures through endoscopic approaches. [ 18 ] Several studies have compared the holmium laser and CKVU in managing short-segment urethral stricture. They have concluded that both techniques are safe and equally effective in treating short-segment urethral strictures in terms of outcome and complication rate.…”
Section: Discussionmentioning
confidence: 99%